2020
DOI: 10.1021/acsomega.0c04734
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Signal Behaviors for Water-in-Oil and Oil-in-Water Emulsions Measured by Resonance-Enhanced Multiphoton Ionization Time-of-Flight Mass Spectrometry

Abstract: Resonance-enhanced multiphoton ionization time-of-flight mass spectrometry (REMPI-TOFMS) was used to study the characteristic signal behaviors obtained from two types of emulsions: water-in-oil (W/O) and oil-in-water (O/W). All emulsions were prepared using phase inversion emulsification, i.e., a solution for an aqueous phase was added dropwise to an oil phase with constant stirring to obtain an emulsion. Toluene served as a detection component. When using REMPI-TOFMS to measure an emulsion, a time profile for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A negative signal based on a base signal indicates that the concentration of styrene at an ionization point is, at the moment, lower than the concentration of styrene in the O 2 phase. In our previous paper, when a W/O emulsion was continuously measured, negative signals based on a base signal were obtained . The emulsion contained toluene as an analyte species, and therefore, negative signals indicated the existence of less-concentrated regions of toluene, i.e., water droplets.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A negative signal based on a base signal indicates that the concentration of styrene at an ionization point is, at the moment, lower than the concentration of styrene in the O 2 phase. In our previous paper, when a W/O emulsion was continuously measured, negative signals based on a base signal were obtained . The emulsion contained toluene as an analyte species, and therefore, negative signals indicated the existence of less-concentrated regions of toluene, i.e., water droplets.…”
Section: Resultsmentioning
confidence: 94%
“…A schematic of the REMPI-TOFMS setup used for this study is shown in Figure . The details of the instrument were reported previously, , and are only briefly described here. The TOFMS setup was developed by Kyushu University, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] Recently, we applied REMPI-TOFMS to the analysis of an emulsion without pretreatment. [23][24][25] In this technique, an emulsion is flowed through a capillary column and is continuously introduced into TOFMS. Then a series of mass spectra are recorded, the peak areas of a target species are extracted from the series of mass spectra, and finally a time profile of the peak areas can be constructed.…”
Section: Introductionmentioning
confidence: 99%